Labour Market in the Czech Republic: DSGE Approach - Martin Železník (Review of Economic Perspectives, 2018)
This paper deals with the comparison of two versions of the DSGE model, supplemented with labour market frictions, based on different data used. One of the data sets has been pre-filtered with the HP filter (lambda set to 1) to get rid of any noise and the other with the original data series with measurement errors allowed. I compare the models with the following tools: parameters estimation, impulse response analysis, standard deviation and cross-correlations and recursive forecast. I also present the historical shock decomposition of the labour market variables to provide the explanation of the development in the Czech labour market, which is considered the most efficient labour market in Europe of the last couple of years with the lowest unemployment rate.
Keywords: 330; DSGE models; labour market; search and matching